El Gobernador constitucional y comandante principal del Departamento de Nuevo Méjico, a sus habitantes : conciudadanos, desde que . (Imprenta del cura de Taos a cargo de J.M. Baca, 1839)
In 1839, hostilities broke out between New Mexico and France over French encroachment into the Mexican territory of Nuevo México. In this proclamation the Governor calls on New Mexican citizens to save their country from the attacks of their enemy.